Effect of Solid Biological Waste Compost on the Metabolite Profile of Brassica rapa ssp. chinensis - Neugart, Susanne; Wiesner-Reinhold, Melanie; Frede, Katja; Jander, Elisabeth; Homann, Thomas; Rawel, Harshadrai M.; Schreiner, Monika; Baldermann, Susanne (Frontiers in Plant Science, 2018)
Large quantities of biological waste are generated at various steps within the food production chain and a great utilization potential for this solid biological waste exists apart from the current main usage for the feedstuff sector. It remains unclear how the usage of biological waste as compost modulates plant metabolites. We investigated the effect of biological waste of the processing of coffee, aronia, and hop added to soil on the plant metabolite profile by means of liquid chromatography in pak choi sprouts. Here we demonstrate that the solid biological waste composts induced specific changes in the metabolite profiles and the changes are depending on the type of the organic residues and its concentration in soil. The targeted analysis of selected plant metabolites, associated with health beneficial properties of the Brassicaceae family, revealed increased concentrations of carotenoids (up to 3.2 fold) and decreased amounts of glucosinolates (up to 4.7 fold) as well as phenolic compounds (up to 1.5 fold).